CAA IMPLEMENTATION ISSUES AND CHALLENGES FOR MINORITY COMMUNITIES IN INDIA AND BORDER STATES - DR.PEER AMIR AHMAD; Dr. S.Balamurugan (RADJA PUBLIKA, 2021)
ABSTRACT The Citizenship Amendment Act, 2019, (Act) narrows India's path to citizenship and calls into question its secular beliefs. This is the first time that India has been designated as a Hindu country. The Act grants Hindu, Christian Sikh, Parsi, Buddhist,, and Jain immigrants from Pakistan, Afghanistan, and Bangladesh Indian citizenship. The legislation offers them citizenship if they arrived in India before December 14, 2014. Due to its multicultural, multilingual, and multi religious communities, India is known for its unity in diversity. This article focuses on the Indian Parliament's approval of the Citizenship Amendment Act of 2019 (CAA) impacting minority populations in India and its neighbouring states. Minority populations in modern South Asian countries suffer a number of challenges. As a result, numerous countries create policies and adopt laws to safeguard the weak. Minorities worldwide form diverse cultures and communities. For nations to transform their organisations and cultures into a civilized world that achieves unity in diversity, empowerment is required. Majority-minority tensions are surfacing at an alarming rate in Asia and Africa's emerging and poor nations. This article examines the flaws in the Indian government's Citizenship Amendment Act of 2019, which discriminates against some minority groups' fundamental rights and the Indian Constitution's secular ethos. This research also aims to address issues that have plagued minority populations since antiquity. South Asian governments and majority-minority organisations are encouraged to use innovative ways. Culture, customs, religion, race, color, caste, and creed separate minorities. This study looks into many facts, causes, and interactions in the Amendment Act of 2019, with an emphasis on religious minorities and their rights. Many issues that impact minority communities in South Asian countries are being investigated for their cause-and-effect relationships.